INFLUENCE OF NON-STATIONARY ELECTROMAGNETIC PROCESSES ON ELECTROMECHANICAL PARAMETERS IN A SYNCHRONOUS ELECTRIC DRIVE - V. V. Zinovkin; M. L. Antonov; Yu. O. Krysan (Elektrotehnìka ta Elektroenergetika, 2018)
Purpose. Investigation of the influence of sharply variable electric load on non-stationary electromagnetic phenomena and electromechanical processes in a synchronous electric drive.